PENGEMBANGAN LKM (LEMBAR KERJA MAHASISWA) PADA KONSEP BIOTEKNOLOGI PANGAN MELALUI PEMBUATAN TAPE SUKUN (Artocarpus altilis) BERDASARKAN LAMA WAKTU FERMENTASI - Yeyen Kaswita Kaswita; Imam Mahadi Mahadi; Sri Wulandari Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The aim of reseach was to determine of result fermermentasi tape breadfruit (Artocarpus altilis) based time fermentationin and development LKM from result fermermentasi tape breadfruit (Artocarpus altilis) in April to June 2015. Results of the research are used for the development of LKM (Students Worksheet) on the concept of food biotechnology. This research was carried out by two phases: the field of research and development phase of LKM (Student Worksheet). Research conducted experiments using completely randomized design (CRD) non factorial, which consists of 6 treatments and 3 replicates in order to obtain 118 experimental design. If there is a real test there will be a further test DMRT 5%. The parameters observed alcohol content, water content, pH, organoleptic taste, aroma and texture. The results showed that long fermentation time a significant effect on alcohol content, water content, pH, organoleptic taste, aroma and texture tape breadfruit (Artocarpus altilis). Long fermentation time of 30 hours is a long time the best fermentation. Where produce alcohol content of 0.943%, 75.48% moisture content and pH 5.02. As for organoleptic taste, aroma and texture of the best there is in the fermentation time of 30 hours. Results of the study can be used as LKM (Students Worksheet) is the fermentation material on the concept of food biotechnology. Keywords: LKM, Food Biotechnology, Tape Breadfruit, Time Fermentation